I would be very grateful if anyone can help
I think I have a way, but i'm a little dubious about it. It involves subtracting f(n) from f(n+1), and factorising out a 4
hint on the induction step:
$\displaystyle (2(n+1)+1)7^{n+1}-1 = (2n+1)7^{n+1} +2\cdot 7^{n+1} -1 = (2n+1)7^n + (2n+1)7^n\cdot 6 +2\cdot 7^{n+1} -1 =$
$\displaystyle = (2n+1)7^n -1 +(2n+1)7^n\cdot 6+ 2\cdot 7^n\cdot(3+4) = (2n+1)7^n -1 +(2n+1)7^n\cdot 6+ 7^n\cdot 6 +8\cdot 7^n = $
$\displaystyle = (2n+1)7^n -1 +(2n+2)7^n\cdot 6 +8\cdot 7^n $
can you follow from here?
do you know how proofs by induction work? Mathematical induction - Wikipedia, the free encyclopedia
1. base case: n=1 ... f(1) = 20 is divisible by 4, base case verified.
2. inductive step: suppose the statement holds for some n. show that the statement holds for n+1. And that is what i've done in the previous post.
Sorry I'm being retarded. Yes I am meant to know how induction works :P I can do the simpler questions, this through me off as it had a n within the bracket as well as the power.
Yes, that makes perfect sense now! Thanks for your help, this has been bugging me!